Effective combination of metal-support for bimetallic catalysts system in ethanol and glycerol reforming: A review - Nor Shafiqah, Mohd Nasir; Sumaiya, Zainal Abidin (2020)
The reliance on fossil fuels to meet the world energy demands throughout these years has led to future insecurity of non-renewable energy sources. Thus, the necessity to provide the energy requirement as we are moving forward falls into renewable and environmentally friendly options. Syngas or hydrogen-based energy rise as potential alternatives credited to high efficiency and clean emissions [1]. In addition, production of hydrogen from biomass keep gaining attention from industrial and academic expertise especially for the reforming technologies. Ethanol and glycerol are emerged as alternatives feedstock for hydrogen production in the last several years due to ethanol is a high hydrogen-containing compound and can be easily derived from renewable biomass resources wheat, sugarcane and organic fractions from forestry residue or municipal [2,3] whereas, glycerol is by product of biodiesel that expected to surplus in amount in near future [4]. Additionally, there are many routes that led to production of syngas or hydrogen namely, steam reforming, partial oxidation, pyrolysis, bi-reforming, CO2 reforming, autothermal reforming, aqueous phase reforming. Ni-based catalysts widely employed in the aforementioned reforming process attributed to its affordable cost compared to noble metals, strong capability of rupturing C-C and C-O bonds and high availability [5]. Nevertheless, Ni-based catalysts tend to deactivate due to carbon formation and thermal Ni sintering [6]. The introduction of bimetallic or polymetallic is one of the significant solutions to reduce carbon formation and catalysts deactivation in reforming process since it can produce more stable catalysts from interaction between two metals [7]. Thus, the aim of this review is to emphasize the application of bimetallic catalysts in glycerol and ethanol reforming based on metal combination. The combination of transition metal will be included the effect of actives site and carbon formation, noble metal pairing will be focused on metal dispersions and transition-noble metal combination will be explained the effect of reduction rate and redox properties as well as the role of support. In addition, the brief explanation of reforming technologies and the summarized findings of structure, classification along with catalysts preparation method will be described in this review.